Principle of entry in the real estate register with reference to the court practice - Tešanović Jelena J. (Zbornik Radova: Pravni Fakultet u Novom Sadu, 2017)
The aim of this paper is to look at the principle of the constitutiveness of entry into the real estate register from the aspect of legal theory and current court practice. Recognizing the existence of certain tendencies to deviate, to a lesser or greater extent, from the provisions of the laws regulating this field, the author draws attention to the possible consequences of such application of the law. The purpose of the entry into public books is in fact to be able to confront registered rights to all third parties in order to ensure their effect erga omnes, contra omnes. This principle is also important when the already existing rights are only published by entry, and especially if the change in the rights is only created by entry. In this respect, the declarative and constitutive character of the registration in the real estate register is discussed. The paper emphasizes that the principle of the constitutiveness of entry should be consistently applied, as the law requires, in the context of other principles of the real estate cadastre and the principles of civil law in general. Only such a court procedure can ensure that the law is the same for everyone, as well as the rule of law and the necessary legal certainty.